Modern Techniques of Rice Production A key for ecosystem sustainability in changing climate - Meena, B. P.; Prasad, Dasharath; Dotaniya, M. L.; Meena, V. D. (Indian Farming, 2015)
Resource Conserving Techniques (RCTs) are more effective in combinations rather than their individual application. SRI method of rice cultivation is an efficient natural resources utilization and it is a solution for enhancing the production and productivity. Among different water-wise rice establishment techniques DSR is cost-effective and gives a higher net return. Sesbania brown manuring is helpful in suppressing weeds and increases the yield. LCC reduced N requirement approximately 25% of applied N. Diversification of rice based cropping sequence is a need of the hour for sustainable production. Site specific nutrient management in rice (SSNM) is helpful to achieve higher yield. Laser land leveling enhances the yield and water productivity.